Google and the “Twisted Cyber Spy” Affair: US–Chinese Communication in an Age of Globalization. - Hartnett, Stephen John (Quarterly Journal of Speech, 2011)
The “twisted cyber spy” affair began in 2010, when Google was attacked by Chinese cyber-warriors charged with stealing Google's intellectual property, planting viruses in its computers, and hacking the accounts of Chinese human rights activists. In the ensuing international embroglio, the US mainstream press, corporate leaders, and White House deployed what I call the rhetoric of belligerent humanitarianism to try to shame the Chinese while making a case for global free markets, unfettered speech, and emerging democracy. That rhetorical strategy carries heavy baggage, however, as it tends to insult the international community, exalt neo-liberal capitalism, sound paternalistic, and feel missionary. Belligerent humanitarianism sounds prudent, however, when compared to the rhetorical strategy of the US military–industrial complex, which marshals the rhetoric of warhawk hysteria to escalate threats into crises and political questions into armed inevitabilities. To counter these two rhetorical strategies, this essay argues that China's leaders deploy the rhetoric of traumatized nationalism, wherein they merge a biting sense of imperial victimage, Maoist tropes of heroism, and a new-found sense of market mastery to portray the US as a tottering land of hypocrisy and China as the rising hope for a new world order. The “Twisted Cyber Spy” affair therefore offers a case study of US–Chinese communication in an age of globalization.